Are in vitro methods for the detection of endocrine potentials in the aquatic environment predictive for in vivo effects? Outcomes of the Projects SchussenAktiv and SchussenAktivplus in the Lake Constance Area, Germany - Henneberg, Anja; Bender, Katrin; Blaha, Ludek; Giebner, Sabrina; Kuch, Bertram; Köhler, Heinz-R; Maier, Diana; Oehlmann, Jörg; Richter, Doreen; Scheurer, Marco; Schulte-Oehlmann, Ulrike; Sieratowicz, Agnes; et al. (PLoS One, 2014)
Many studies about endocrine pollution in the aquatic environment reveal changes in the reproduction system of biota. We analysed endocrine activities in two rivers in Southern Germany using three approaches: (1) chemical analyses, (2) in vitro bioassays, and (3) in vivo investigations in fish and snails. Chemical analyses were based on gas chromatography coupled with mass spectrometry. For in vitro analyses of endocrine potentials in water, sediment, and waste water samples, we used the E-screen assay (human breast cancer cells MCF-7) and reporter gene assays (human cell line HeLa-9903 and MDA-kb2). In addition, we performed reproduction tests with the freshwater mudsnail Potamopyrgus antipodarum to analyse water and sediment samples. We exposed juvenile brown trout (Salmo trutta f. fario) to water downstream of a wastewater outfall (Schussen River) or to water from a reference site (Argen River) to investigate the vitellogenin production. Furthermore, two feral fish species, chub (Leuciscus cephalus) and spirlin (Alburnoides bipunctatus), were caught in both rivers to determine their gonadal maturity and the gonadosomatic index. Chemical analyses provided only little information about endocrine active substances, whereas the in vitro assays revealed endocrine potentials in most of the samples. In addition to endocrine potentials, we also observed toxic potentials (E-screen/reproduction test) in waste water samples, which could interfere with and camouflage endocrine effects. The results of our in vivo tests were mostly in line with the results of the in vitro assays and revealed a consistent reproduction-disrupting (reproduction tests) and an occasional endocrine action (vitellogenin levels) in both investigated rivers, with more pronounced effects for the Schussen river (e.g. a lower gonadosomatic index). We were able to show that biological in vitro assays for endocrine potentials in natural stream water reasonably reflect reproduction and endocrine disruption observed in snails and field-exposed fish, respectively.
Keywords: monitorování životního prostředí; Cell Line; In Vitro Techniques; Snails; ekotoxikologie; Environmental Monitoring; techniky in vitro; vitelogeniny; Německo; endokrinní disruptory; řeky; Rivers; chemické látky znečišťující vodu; hlemýždi; Water Pollutants, Chemical; Endocrine Disruptors; zvířata; Humans; Germany; buněčné linie; Fishes; ryby; Vitellogenins; Ecotoxicology; lidé; Animals